THE DEVELOPMENT AND DYNAMICS OF ISLAMIC JUSTICE IN VARIOUS ISLAMIC COUNTRIES: SAUDI ARABIA, EGYPT, YEMEN, AND SUDAN - Nur Rohim, M. Yusuf (DE'RECHTSSTAAT, 2024)
This article discusses the dynamics of Islamic justice in various Islamic countries such as Saudi Arabia, Egypt, Yemen and Sudan. All these countries have the same reference in implementing Islamic law in their judiciary, namely referring to the Al-Quran and Hadith. The research method used in preparing this article is a comparative study by comparing the similarities and differences of several Islamic countries: Saudi, Egypt, Yemen, & Sudan in terms of the implementation of Islamic justice which is researched through reading materials including books, laws and regulations, and various other related sources.